2018
DOI: 10.1021/acsbiomaterials.8b00277
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Zinc Oxide/Poly(Lactic Acid) Nanocomposite Layer Coated on Magnesium Alloys for Controlled Degradation and Antibacterial Function

Abstract: In the present work, magnesium (Mg) AZ31 alloy was coated with a multifunctional membrane layer composed of ZnO nanoparticles (NPs) embedded in a poly­(lactic acid) (PLA) matrix. We aimed to produce a stable coating that would be used to control the degradation rate of the Mg alloy and promote a local antibacterial activity. ZnO NPs were dispersed at 5 and 10 wt % in a PLA solution and dip-coated onto the AZ31 substrate. Surface topography, chemical composition, thickness, electrochemical corrosion performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 65 publications
0
41
0
1
Order By: Relevance
“…Therefore, it is necessary to control the degradation rate of magnesium alloys for realizing long-term implantation. At present, surface modifications are considered to be an effective way to improve the corrosion resistance of magnesium alloys [ 9 , 10 , 11 , 12 , 13 , 14 ]. Among all of the various surface modifications, the MAO coatings have been widely employed on Mg alloys due to its metallurgical adhesion to the substrate, good wear resistance, moderate corrosion resistance, and high hardness [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to control the degradation rate of magnesium alloys for realizing long-term implantation. At present, surface modifications are considered to be an effective way to improve the corrosion resistance of magnesium alloys [ 9 , 10 , 11 , 12 , 13 , 14 ]. Among all of the various surface modifications, the MAO coatings have been widely employed on Mg alloys due to its metallurgical adhesion to the substrate, good wear resistance, moderate corrosion resistance, and high hardness [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from antibacterial activities, non‐toxicity is also identified as an most essential requirement in the biomedical application for thermosensitive and antibacterial materials . The cytotoxicity of the synthesized polyamides was evaluated using the typical HeLa cells by MTT method in this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in vitro showed that the mouthwash solution containing TiO 2 NPs showed superior antibacterial activity against oral pathogenic microorganisms [151]. Nanoparticles of Zn [152,153], Ag [2,154,155,156,157,158,159,160] synergistic with CHX [161,162] or doxycycline [163] showed significant antibacterial effect in an in vitro subgingival biofilm mode. Hexagonal form of boron nitride (hBN)—referred as “white graphite”—showed high antibiofilm activity on preformed biofilm and exhibited no cytotoxic effect on cells at the concentration range of 0.025–0.1 mg/mL [164].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%